2014
DOI: 10.1155/2014/964365
|View full text |Cite
|
Sign up to set email alerts
|

Unaffected Arm Muscle Hypercatabolism in Dysphagic Subacute Stroke Patients: The Effects of Essential Amino Acid Supplementation

Abstract: Alterations in muscle protein turnover of the unaffected side of stroke patients could contribute to physical disability. We investigated whether hypercatabolic activity occurred in unaffected arm muscle and whether supplemented essential amino acids (EAAs) could limit muscle hypercatabolism (MH). Thirty-eight dysphagic subacute stroke subjects (<3 months after acute event) (29 males + 9 females; 69.7 ± 11.4 yrs) were enrolled and randomized to receive 8 g/day EAAs (n = 19; EAA group) or isocaloric placebo (ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…Secondly, the patients’ high levels of the AAs that are not metabolised by muscle, such as phenylalanine, tyrosine, lysine and methionine, are indicative of a state of muscle hypercatabolism. A previous investigation showed that the ipsilateral arm (= unaffected) in stroke patients had a net release of phenyalanine [9]. Thirdly, high serum CRP suggests increased Interleukine 6 production [44], which promotes muscle protein breakdown by several mechanisms including both inhibition of muscle protein synthesis, repair, contractility and function [45], and stimulation of the hypothalamus-pitituary-cortical axis leading to increased cortisol production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the patients’ high levels of the AAs that are not metabolised by muscle, such as phenylalanine, tyrosine, lysine and methionine, are indicative of a state of muscle hypercatabolism. A previous investigation showed that the ipsilateral arm (= unaffected) in stroke patients had a net release of phenyalanine [9]. Thirdly, high serum CRP suggests increased Interleukine 6 production [44], which promotes muscle protein breakdown by several mechanisms including both inhibition of muscle protein synthesis, repair, contractility and function [45], and stimulation of the hypothalamus-pitituary-cortical axis leading to increased cortisol production.…”
Section: Discussionmentioning
confidence: 99%
“…This may contribute to explaining the inverse correlation between glycin and Hb. The high value of plasma glycin found in stroke subjects was probably due to muscle release following protein overdegradation [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunonutrients can promote patient recovery by inhibiting inflammatory responses and regulating immune function. Glutamine, which can modulate and preserve intestinal and lung function, is compromised in conditions of severe stress, reducing the production of pro-inflammatory cytokines [ 9 , 10 ]. Cytokine-mediated effects are an essential part response to infection but excessive production of pro-inflammatory cytokines increases the risk of pneumonia and death in COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
“…This study highlights the importance in sub-acute stroke individuals of monitoring blood N/Lymph ratio over time. Strictly linked to this factor is preventing infection which may be of fundamental importance to avoid the aggravation of patient muscle hypercatabolism 24 which could also affect deglutition musculature. The N/Lymph ratio may be more useful than CRP in understanding the courses of clinical- metabolic- functional status.…”
Section: Discussionmentioning
confidence: 99%